2019
DOI: 10.1080/17522439.2019.1578401
|View full text |Cite
|
Sign up to set email alerts
|

ACT in daily life in early psychosis: an ecological momentary intervention approach

Abstract: The current article describes the Acceptance and Commitment Therapy (ACT) in Daily Life (ACT-DL) training, a new mobile health treatment protocol for ACT applied in a randomized controlled trial in early psychosis individuals. Between weekly ACT therapy sessions, patients fill out brief questionnaires on an app about their mood, symptoms, activity, and current context, thus promoting awareness-a crucial component of ACT. The app also provides them with visual cues and exercises specifically related to the ACT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 28 publications
0
70
0
5
Order By: Relevance
“…The acceptance and commitment therapy in daily life (ACT-DL) study [29] utilized a subset of participants to determine the feasibility of an ongoing randomized controlled trial, which plans to enroll 150 participants into the program. The ACT-DL app offers ACT toward improving negative symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptance and commitment therapy in daily life (ACT-DL) study [29] utilized a subset of participants to determine the feasibility of an ongoing randomized controlled trial, which plans to enroll 150 participants into the program. The ACT-DL app offers ACT toward improving negative symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The 16 participants to date found both the ACT therapy sessions and the home exercises useful. They also reported that the app helped them implement ACT into their daily life and helped bring awareness to their emotions [29].…”
Section: Resultsmentioning
confidence: 99%
“…The manualised ACT-DL intervention consists of eight ACT training sessions (including one session for psychoeducation) administered face-to-face by a trained clinician (i.e. psychologists having received a 5-day training in ACT-DL and receiving fortnightly supervision sessions for the purposes of the trial), each for around 45–60 min, and an ACT-based EMI, which participants will receive following randomisation to the experimental condition [46], over an 8-week intervention period. The latter will be administered through a smartphone-based app (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Delivering ACT and evaluating its effects on putative mechanisms in daily life based on principles of EMIs is, therefore, both timely and eminently important. Acceptance and Commitment Therapy in Daily Life (ACT-DL) has recently been developed for enhancing the therapeutic effects of ACT under real-world conditions [28–30, 46]. ACT may be particularly amenable to be implemented as an EMI, as it emphasises the context in which a behavior occurs as well as the function of this behavior in a given context [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation